Urinary Iodine Excretion of Lactating Mothers Predicts the Iodine Content of Their Breast Milk - Molla, Golam Morshed; Arslan, M Iqbal; Mollah, Forhadul Hoque; Khan, Md Aminul Haque; Jinnah, Chaklader Md Kamal (Journal of Enam Medical College, 2012)
Background: Iodine is essential for normal growth, mental development and survival of infants. Bangladesh is an iodine deficient region. Breast milk is the only source of iodine for exclusively breast-fed infants. Routine measurement of breast milk iodine concentration is very difficult in our country due to some social and religious barriers. So, we designed this study in our population using urinary iodine as the indicator for assessing iodine status. Objectives: To assess the iodine status of lactating mothers and their breast-fed infants and to propose a method on how to predict the iodine concentration in breast milk. Materials and Methods: This observational analytical study was carried out in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka with active cooperation of Kumudini Womens Medical College Hospital, Mirzapur, Tangail involving fifty lactating mothers and their exclusively breast-fed infants. Early morning urine and breast milk samples were collected in dry and clean plastic container free from any chemical contamination. All statistical analyses were done by using SPSS (Statistical Programme for Social Science) 12 version software package for windows. Results: The median (range) urinary iodine concentration of lactating mothers and their breast-fed infants were 225.25 ?g/L (61.50-530.00) and 225.75 ?g/L (100.50-526.50). 96% (48) mothers had no biochemical iodine deficiency (UIE ?100?g/L), only 4% (2) mothers had mild biochemical iodine deficiency (UIE 50-99?g/L). There was no biochemical deficiency of breast-fed infants. The median (range) breast-milk iodine concentration was 157 ?g/L (54.50-431.50) which was more than three times of recommended minimum concentration (50 ?g/L). Iodine in breast milk of lactating mothers positively correlated with their urinary iodine excretion (P<0.01). Infants urinary iodine positively correlated with iodine concentration in breast milk (P<0.01) and also positively correlated with urinary iodine excretion of lactating mothers. Conclusion: Lactating mothers and their breast-fed infants in this study were found iodine sufficient. Urinary iodine concentration of lactating mothers predicts the iodine content of their breast milk. DOI: http://dx.doi.org/10.3329/jemc.v1i1.11132 J Enam Med Col 2011; 1(1): 15-18